STUDI PERKEMBANGAN STRUK TUR KOMUNITAS IKAN KARANG DI TERUMBU BUATAN BERBENTUK HEXADOME PADA BERBAGAI KONDISI PERAIRAN DI KABUPATEN BULELENG, BALI - YUNALDI, YUNALDI; Arthana, I Wayan; ASTARINI, IDA AYU (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2011)
Artificial reefs are made to act as temporary substitutes for small areas of damaged original reef. The structures attract fish and other marine organisms, which can eventually be exploited (e.g. for human food), so it is expected that they will form the basis around which natural reefs can grow and recover. The purpose of this study is to document recruitment of organisms onto the artificial structures, evaluate the effectiveness of the structures in terms of shape and recruitment potential, and use the recruitment information to show which species occur in the surrounding reefs. This research was conducted from May-July 2010 in north Bali, in the Village District Gerokgak Patas, Kampung Baru Village in Buleleng District, and Penuktukan Village, Kecematan Tejakula. The research method used was a visual census method to determine the number of fish species and fish abundance on artificial reefs at three different locations. Three replications were performed at each location. 2481 individuals from 18 families (38 species) of reef fish were observed. The area with the greatest abundance of fish and the highest number of fish species was in Kampung Baru, with 1170 individuals from 21 species of fish. Dominant reef fish species were Plotosus lineatus (Cat Fish) - 510 individuals, Pomacentrus auriventris (Goldbelly damsel)- 256 individuals, Dascyllus trimaculatus (Three spot damsel) - 335 individuals, Pseudanthias squamipinnis (Lyretail Anthias) - 320 individuals. A Sorensen analysis showed that reef fish communities on the artificial reefs in the form of 'hexadomes' were not derived from the surrounding reefs.
Keywords: hexadome, artificial reefs, reef fishes